Stability of a frame-based oldest-cell-first maximal weight matching algorithm - Xike Li; Elhanany, I. (IEEE transactions on communications, 2008)
Input-queued cell switches employing the oldest-cell-first (OCF) policy have been shown to yield low mean delay characteristics. Moreover, it has been proven that OCF is stable for admissible traffic conditions when executed with a scheduling speedup of 2. However, as link speeds increase, the computational complexity of these algorithms limits their applicability in high port-density switches and routers. To address the scalability issue, we describe a Frame-Based Maximal Weight Matching (FMWM) algorithm, employing OCF as queue weights, in which a new scheduling decision is issued once every several cell times. Between scheduling decisions, the configuration of the crossbar switch remains unchanged. We further extend the analysis to address the case of multiple classes of service, and prove that the algorithm is stable with an internal buffer transfer speedup of 2, thereby significantly relaxing the timing constraints imposed on the scheduling process.